Small industry development programme - "Vepa , Ram K." (New Delhi, 1983)
In recent years there has been an increasing recognition of the role small industry can play in effecting growth of the national economy. Many developing countries are formulating and implementing special programmes for the development of small industry in their countries with a view to providing new employment oppurtunities, transfer industries to the rural and semi- urban areas and also provide outlets for the creative energies of the younger people.
Keywords: Industry and state India